Green regenerated rubber anti-seismic and anti-impact ultra-high performance concrete

By using green recycled rubber powder and recycled steel fibers in ultra-high performance concrete, the shortcomings of traditional ultra-high performance concrete in terms of earthquake resistance and impact resistance are solved, and higher impact and earthquake resistance are achieved, while having environmental protection and economical advantages.

CN119899006APending Publication Date: 2025-04-29SUZHOU HONGCORAL CONSTRUCTION WASTE REGENERATION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510081340.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Traditional ultra-high performance concrete has shortcomings in its earthquake resistance and impact resistance, and it is difficult to effectively absorb and dissipate impact energy, resulting in poor earthquake resistance.

Method used

Green recycled rubber powder and recycled steel fibers are used to replace traditional materials. By recycled rubber powder and recycled steel fibers, the working performance and impact resistance of concrete are optimized.

Benefits of technology

It significantly improves the static and dynamic impact resistance of ultra-high performance concrete, enhances its earthquake resistance, reduces preparation costs and raw material energy consumption, and at the same time achieves long-term carbon sequestration, which has good environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899006A_ABST
    Figure CN119899006A_ABST
Patent Text Reader

Abstract

The invention discloses green regenerated rubber anti-seismic and anti-impact ultra-high performance concrete, and belongs to the field of concrete materials. The green regenerated rubber anti-seismic and anti-impact ultra-high performance concrete is prepared from the following raw materials in parts by weight: 924 parts of cement, 176 parts of silica fume, 150 parts of fly ash, 498.5 parts of natural river sand, 399 parts of machine-made sand, 27.5 parts of regenerated rubber powder, 20 parts of an efficient polycarboxylate superplasticizer, 148.5 parts of regenerated steel fibers and 212.5 parts of water. Compared with the prior art, the concrete material disclosed by the invention has better anti-seismic property, the viscosity of concrete mortar is lower, the flowability is higher, and the early shrinkage of the material is also controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of concrete materials, and in particular to a green recycled rubber earthquake-resistant and impact-resistant ultra-high performance concrete. Background Art

[0002] Ultra-high performance concrete (UHPC) is a new type of cement-based composite material with the characteristics of lightweight, ultra-high strength, ultra-high ductility, ultra-high durability and impact resistance. It has broad application prospects in the field of civil engineering. Although traditional ultra-high performance concrete has relatively excellent impact resistance, it is still based on a "hard-on-hard" approach, relying on the ultra-high strength of the ultra-high performance concrete substrate to resist external impact loads. During an earthquake, the structure needs to be able to effectively absorb and dissipate impact energy to exert its earthquake resistance. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention proposes a green recycled rubber seismic and impact-resistant ultra-high performance concrete.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] The first aspect of the present invention relates to a green recycled rubber seismic and impact resistant ultra-high performance concrete, comprising the following raw materials in parts by weight:

[0006] 924 parts of cement, 176 parts of silica fume, 150 parts of fly ash, 498.5 parts of natural river sand, 399 parts of machine-made sand, 27.5 parts of recycled rubber powder, 20 parts of high-efficiency polycarboxylic acid water-reducing agent, 148.5 parts of recycled steel fiber and 212.5 parts of water.

[0007] Optionally, the regenerated rubber powder is obtained by tearing, crushing, grinding and then sieving waste tires.

[0008] Optionally, the regenerated steel fiber is steel cord taken from waste tires and obtained after tearing and screening.

[0009] Optionally, the stone powder content in the machine-made sand is 7.0% to 15.0%, and the fineness modulus is 2.5.

[0010] The second aspect of the present invention relates to a method for preparing a green recycled rubber seismic and impact-resistant ultra-high performance concrete, comprising the following steps: taking the following raw materials in parts by weight: 924 parts of cement, 176 parts of silica fume, 150 parts of fly ash, 498.5 parts of natural river sand, 399 parts of machine-made sand, and 27.5 parts of recycled rubber powder, stirring and mixing, adding 148.5 parts by weight of recycled steel fiber, continuing to stir, and then adding 20 parts by weight of a high-efficiency polycarboxylic acid water reducer and 212.5 parts by weight of water.

[0011] Optionally, pouring and curing steps are also included.

[0012] Optionally, the regenerated rubber powder is obtained by tearing, crushing, grinding and then sieving waste tires.

[0013] Optionally, the regenerated steel fiber is steel cord taken from waste tires and obtained after tearing and screening.

[0014] Beneficial effects of the present invention:

[0015] (1) In the ultra-high performance concrete, the recycled rubber powder replaces the natural fine aggregate in a large amount at a volume replacement rate of 10%, thereby improving the static and dynamic impact resistance of the ultra-high performance concrete; (2) The large amount of recycled rubber powder optimizes the working performance of the ultra-high performance concrete material, making the viscosity of the ultra-high performance concrete mortar lower and the fluidity greater, and the early shrinkage of the material is also controlled; (3) The large amount of recycled rubber powder absorbed by ultra-high performance concrete can achieve long-term carbon fixation and produce good environmental benefits; (4) The recycled steel fiber extracted from waste tires is used to replace the industrial steel fiber in the ultra-high performance concrete, which not only exerts its reinforcing, toughening and crack-proof effects, but also effectively reduces the preparation cost and raw material energy consumption of the ultra-high performance concrete; (5) The processing and preparation methods are simple, and the recycled rubber and recycled fiber can be recycled by crushing and screening, without the need for cracking, deep processing and modification. The ultra-high performance concrete pouring process does not require the introduction of additional modified admixtures, which is easy to industrialize and mix on site. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a picture of recycled rubber powder obtained after the crushing and screening of waste tires;

[0017] Figure 2 The gradation curve of machine-made sand particles used in green recycled rubber seismic and impact-resistant ultra-high performance concrete;

[0018] Figure 3 This is the static compressive failure stress-strain curve of the green recycled rubber seismic and impact resistant ultra-high performance concrete compression specimen;

[0019] Figure 4 This is a photo of the static compression failure specimen of the green recycled rubber seismic and impact resistant ultra-high performance concrete compression specimen;

[0020] Figure 5 Among them, (1) is the compressive stress-strain curve of the green recycled rubber seismic and impact resistant ultra-high performance concrete impact-resistant specimen; (2) is the dynamic impact failure strength bar graph of the green recycled rubber seismic and impact resistant ultra-high performance concrete impact-resistant specimen;

[0021] Figure 6 This is a real photo of the dynamic impact destruction specimen of the green recycled rubber seismic and impact-resistant ultra-high performance concrete impact-resistant specimen. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The present invention provides a technical solution: the present invention discloses a green recycled rubber seismic and impact resistant ultra-high performance concrete, comprising the following raw materials in parts by weight: 924 parts of cement, 176 parts of silica fume, 150 parts of fly ash, 398 parts of machine-made sand, 27.4 parts of recycled rubber powder, 20 parts of polycarboxylic acid high-efficiency water reducing agent, 148.5 parts of recycled steel fiber and 212.5 parts of water.

[0024] The recycled rubber powder is recycled from waste tires by crushing and grinding, and the particle size is 40 to 60 mesh. Figure 1 shown.

[0025] The fine grinding process is to use a planetary ball mill for mechanical crushing and grinding, with a rotation speed of 2500 rpm and a grinding time of 2 minutes.

[0026] The regenerated steel fiber is made of recycled steel fiber with a length of 13 mm, a diameter of 0.22 mm, and an aspect ratio of 60 after crushing and screening of waste tires, and has a tensile strength of 1.8 to 2.0 GPa. Figure 1 shown.

[0027] The cement is silicate cement with a strength grade of 52.5.

[0028] The water reducer is a polycarboxylic acid high-efficiency water reducer, which was purchased from Shanxi Kangtel Fine Chemical Co., Ltd.

[0029] The fly ash is first-grade fly ash with a particle size of 13 μm.

[0030] The machine-made sand is produced by crushing and screening the waste rock produced by coal mining. The stone powder content in the machine-made sand is 7.0% to 15.0%, the fineness modulus is 2.5, and it belongs to Class I II zone machine-made sand. The particle diameter distribution is as follows: Figure 2 shown.

[0031] According to the specimen mix ratio in Table 1, the control example (conventional ultra-high performance concrete piece) and the embodiment specimens were prepared by the following steps.

[0032] S1 Pour the powder materials in the prescribed proportion: cement, silica fume, fly ash, natural river sand, machine-made sand and recycled rubber powder into a forced mixer and mix them evenly for 3 minutes, then slowly add steel fiber and continue mixing for 2 minutes;

[0033] S2 slowly adds water reducer and water to the mixer, stirs for 6 minutes, casts the specimen and compacts it on a vibration table. During the casting process, cast twice to prevent rubber particles from floating up;

[0034] After S3 pouring, the surface was plastered about 1 hour before initial setting. To avoid water evaporation, the surface of the specimen was covered with a film. After standing at 20°C for 24 hours, the mold was removed and the specimen was placed in a high-temperature water bath for 90°C hot water for 72 hours. After that, it was cured under standard conditions for 28 days to obtain green recycled rubber seismic and impact-resistant ultra-high performance concrete.

[0035] Table 1: Proportion of Comparative Example 1 and Example Test Pieces

[0036]

[0037] Among them, the control example 1 is an ultra-high performance concrete mix ratio without the addition of recycled rubber, recycled steel fiber and machine-made sand. The fluidity of the control example 1 is 93.5 mm, and the fluidity of the embodiment is 158.8 mm. The working performance of the mortar meets the construction requirements. The preferred group of mortars with rubber particles has better fluidity, is easier to pump and fully fills the structural gaps.

[0038] According to GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the control example and the embodiment were cured for different days. After the curing was completed, the slump of the freshly mixed mortar and the compressive strength of the specimens were tested. Among them, the fluidity of the control example was 93.5mm, and the fluidity of the preferred group was 158.8mm. The working performance of the mortar met the construction requirements. The preferred group had better fluidity, was easier to pump and fully filled the structural gaps, and the static compressive strength σ of the specimens was 1.38mm. s As shown in Table 2.

[0039] Table 2 Static compressive strength comparison table

[0040]

[0041] The static compressive stress-strain curve of the specimen is shown in Figure 3 As shown in the figure, the corresponding physical photos of the damage degree of the specimens in different stages are shown in Figure 4 When the specimens of control example 1 and embodiment are destroyed, the corresponding strain ε when the compressive stress reaches the peak value is cBoth are over 0.02, much higher than 0.002-0.003 of general concrete; the mechanical properties of the control example 1 specimen in the destruction stage show obvious brittle characteristics, the elastic energy drops rapidly when under pressure, the integrity of the specimen after destruction is poor, the trend of surface cracks is relatively straight and densely formed into a damage zone; the embodiment specimen has improved its toughness due to the flexible energy consumption of recycled rubber powder, and shows the mechanical characteristics of brittle-ductile conversion in the destruction stage. The elastic potential energy slowly decreases when under pressure, and the specimen after destruction is "broken but not scattered", with fewer cracks and better integrity. Materials with better ductility can better withstand seismic loads. The test results show that the combined synergistic effect of recycled rubber and recycled steel fiber can better increase the static toughness of ultra-high performance concrete, so that when it reaches the stress peak and is destroyed, the stress slowly drops to the residual strength, showing better ductility characteristics and excellent seismic performance.

[0042] According to the mix ratio of comparative example 1 and the embodiment in Table 1, a cylindrical specimen (casting specimen) with a diameter of 74 mm and a height of 37 mm was prepared. After curing for 28 days, the specimen was finely ground several times using a double-end grinder, and finally a dynamic vibration and impact resistance specimen with a height-to-diameter ratio of 0.5 and an angle between the normal direction of the specimen end face and the axis of less than 0.25° was prepared.

[0043] The polished high-speed impact test specimen was placed in a Φ80mm split Hopkinson pressure bar (SHPB) system to carry out a dynamic impact test. The pressure bar was driven by high-pressure nitrogen to impact the specimen. The nitrogen pressure was 2.0MPa, 2.7MPa, and 3.5MPa, and the corresponding speeds were 11.46m / s, 13.34m / s, and 15.77m / s, respectively. The dynamic enhancement factor of the specimen under different impact speeds is shown in Table 3.

[0044] Table 3 Comparison table of dynamic compressive strength and enhancement factor

[0045]

[0046]

[0047] Under the action of the impact stress wave, the strain ε(t), strain rate η(t) and stress σ(t) of the specimen are:

[0048]

[0049] Where: C 0 is the elastic wave velocity of the stress wave in the compression rod, L is the initial length of the specimen, A and A s are the cross-sectional areas of the compression rod and the specimen, E is the elastic modulus of the compression rod, ε r (t) and ε t (t) represent the reflected wave and transmitted wave signals measured by the strain gauge at a certain time t.

[0050] The peak value of σ(t) is the dynamic compressive strength σ of the specimen. d .

[0051] Dynamic enhancement factor DIF of the specimen:

[0052] DIF=σ d / σ s (4)

[0053] Where: s Represents the static compressive strength of the specimen, σ d It represents the dynamic compressive strength of the specimen, and DIF is the dynamic enhancement factor of the specimen under impact load.

[0054] The dynamic impact compression stress-strain curve of the specimen is shown in Figure 5 As shown in (1), the impact compression process can be divided into four stages: compaction stage, elastic stage, yield stage, and destruction stage. In the yield stage, the plastic deformation of the specimen increases rapidly, through cracks appear inside, and the stress value reaches the peak strength; when the peak strain is reached, the stress begins to drop rapidly, the cracks in the specimen fully develop and penetrate, and fragmentation occurs. Energy evolution analysis shows that recycled rubber effectively improves the dynamic impact toughness of the specimen by reducing the system reflection energy and increasing the dissipated energy. The dynamic compressive strength of the specimen at different impact velocities is shown in Figure 5 (2) shows the actual photo of the specimen damaged after high-speed impact. Figure 6 shown.

[0055] Table 4: Raw material ratios of comparative examples 2 to 10

[0056]

[0057] In addition, the present invention also provides control examples 2 to 10, which are ultra-high performance concrete mixes with adjusted water-cement ratio, recycled rubber powder, machine-made sand, and steel fiber dosage in addition to the preferred embodiment mixes. The specific data are shown in Table 4.

[0058] The test data show that although reducing the water-cement ratio, the amount of recycled rubber powder and increasing the amount of machine-made sand and steel fiber outside the preferred mix ratio can improve the concrete strength to a certain extent, it will also cause a significant decrease in the fluidity of the mortar, affecting the construction performance of ultra-high performance concrete; increasing the water-cement ratio and the amount of recycled rubber powder and reducing the amount of machine-made sand and steel fiber outside the preferred mix ratio can improve the construction performance of concrete, it will also cause a significant decrease in the strength of the specimens.

[0059] Other measured data show that the addition of rubber particles can also improve the autogenous shrinkage characteristics of the specimens. The static compressive strength σ s The early autogenous shrinkage is shown in Table 5.

[0060] Table 5 Comparison of static compressive strength and early autogenous shrinkage

[0061]

[0062] In summary, it can be seen from the experimental data of this application that the seismic and impact-resistant ultra-high performance concrete prepared by using 10% recycled rubber, 40% machine-made sand volume to replace natural fine aggregate and 2% recycled steel fiber to replace cementitious materials, although the strength is reduced, can basically meet the mechanical requirements of ultra-high performance concrete in engineering. In the static test, at the peak of the impact compression strength of the embodiment, the strain ε d It is 0.008-0.012, which is much higher than 0.003-0.006 of the control example. The results show that the recycled rubber powder particles effectively improve the deformation capacity and ductility of ultra-high performance concrete. When compressed and destroyed, the microcracks of the embodiment specimens are finer and denser, and the germination rate of visible cracks is slower. In the dynamic impact test of the compression rod, the recycled rubber powder particles mixed in the ultra-high performance concrete can absorb more instantaneous elastic deformation energy, significantly improving the impact resistance of the ultra-high performance concrete. The higher the impact speed, the more obvious the dynamic toughening effect. The improvement of impact resistance and toughness enables ultra-high performance concrete to not only directly resist seismic loads, but also resist and weaken various secondary disasters such as superstructure collapse, falling, gas leakage and explosion caused by strong earthquakes, so as to better protect people’s lives and property safety.

[0063] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0064] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A green recycled rubber seismic and impact resistant ultra-high performance concrete, characterized in that: It includes the following raw materials in parts by weight: 924 parts of cement, 176 parts of silica fume, 150 parts of fly ash, 498.5 parts of natural river sand, 399 parts of machine-made sand, 27.5 parts of recycled rubber powder, 20 parts of high-efficiency polycarboxylic acid water-reducing agent, 148.5 parts of recycled steel fiber and 212.5 parts of water.

2. The green recycled rubber seismic and impact resistant ultra-high performance concrete according to claim 1, characterized in that: The regenerated rubber powder is obtained by tearing, crushing, grinding and then sieving waste tires.

3. The green recycled rubber seismic and impact resistant ultra-high performance concrete according to claim 1, characterized in that: The regenerated steel fiber is obtained by tearing and screening the steel cords from waste tires.

4. The green recycled rubber seismic and impact resistant ultra-high performance concrete according to claim 1, characterized in that: The stone powder content in the machine-made sand is 7.0% to 15.0%, and the fineness modulus is 2.

5.

5. A method for preparing green recycled rubber seismic and impact-resistant ultra-high performance concrete, characterized in that: The following steps are involved: Take the following raw materials in parts by weight: 924 parts of cement, 176 parts of silica fume, 150 parts of fly ash, 498.5 parts of natural river sand, 399 parts of machine-made sand, and 27.5 parts of recycled rubber powder, stir and mix, then add 148.5 parts by weight of recycled steel fiber, continue stirring, and then add 20 parts of high-efficiency polycarboxylic acid water reducer and 212.5 parts by weight of water.

6. The method for preparing green recycled rubber seismic and impact resistant ultra-high performance concrete according to claim 5, characterized in that: It also includes pouring and curing steps.

7. The method for preparing green recycled rubber seismic and impact resistant ultra-high performance concrete according to claim 5, characterized in that: The regenerated rubber powder is obtained by tearing, crushing, grinding and then sieving waste tires.

8. The method for preparing green recycled rubber seismic and impact resistant ultra-high performance concrete according to claim 5, characterized in that: The regenerated steel fiber is obtained by tearing and screening the steel cords from waste tires.